On the necessity of joint adoption of both Distributed Maximum Power Point Tracking and Central Maximum Power Point Tracking in PV systems. (9th July 2012) - Vitelli, Massimo
ABSTRACT In this paper, the main causes that are able to limit the efficiency of Distributed Maximum Power Point Tracking (DMPPT) are analyzed in detail. It will be shown that, to get full profit from DMPPT, it is necessary that the bulk inverter voltage belongs to an optimal range whose position and amplitude are functions of the following factors: the number of PV modules and dedicated DC/DC converters in a string, the atmospheric operating conditions characterizing each PV module (irradiance and temperature values), the voltage and current ratings of the physical devices the DC/DC converters are made of, and the adopted DC/DC converter topology. Moreover, it will be given proof of the necessity to couple the DMPPT function with a suitable centralized MPPT function carried out by the inverter through the proper control of its own DC input voltage. Copyright © 2012 John Wiley & Sons, Ltd.